اسلامی تصورِ احتساب اور عدلیہ پر اس کا اطلاق - Kh. Awais Ahmed Khawaja (الضحی, 2021)
Accountability has a very significant role in Islamic law. The process of accountability is very important for the amelioration of the state, society, family, and individual in the world. Some orders are issued for rectification and some matters are ordered to be avoided. The execution of these prohibited acts leads to accountability in society. Furthermore, many people are given powers to carry out the affairs of the state, the misuse of which can lead to great catastrophe. Hence, it is very critical to hold accountable those who hold these positions from time to time. One of these influential positions is that of the judiciary to which the Islamic concept of accountability is very substantial. Now the question is, what is the concept of accountability in Islam? And what was the exercise of accountability of the judiciary in the Qur'an and Hadith and Islamic history? This matter will be discussed in this manuscript. This research will refer to the introduction of accountability using authoritative citations to illustrate the Islamic concept of accountability, its sources, and strategies. How did accountability apply to the judiciary in Islamic history? Specimens are also included in this study and will be discussed. The importance of this research and its results will be disclosed in the conclusion. We will know that Islamic law has comprehensive laws of accountability, and how this sector has been kept on the right track by applying the law of accountability to the judiciary in the past.